The Role of Elementary School Students of Soro Village in Preserving Kakara Culture in the Lariti Beach Mangrove Ecotourism, Lambu District, Bima Regency - Ihsan, Ihsan (Universitas Tanjungpura, 2025)
Indonesia, as an archipelagic nation, has abundant coastal cultural heritage inherited from generation to generation. One of these traditions is Kakara, a local wisdom of the Soro Village community in Bima Regency, where people catch fish, shellfish, and crabs during low tide using traditional tools. This research aims to analyze the role of Madrasah Ibtidaiyah students in preserving the Kakara culture, measure the effectiveness of educational programs to increase awareness, and formulate sustainable collaboration strategies among schools, communities, and local governments. This qualitative research uses an ethnographic approach with purposive sampling involving 50 students and local residents. Data were collected through participatory observation, interviews, questionnaires, and Focus Group Discussions (FGD), and analyzed using NVivo software. The results show that 75% of students understand Kakara as a cultural activity, 50% have participated directly, and 87.5% of community members are still active in this tradition. The NVivo analysis identified four dominant nodes: cultural understanding, youth participation, preservation challenges, and preservation strategies. The most dominant node—preservation strategy—indicates the importance of integrating Kakara into school learning, organizing annual cultural festivals, and strengthening cross-sector collaboration. Kakara remains relevant as a medium for cultural education and environmental awareness.